JOB SATISFACTION: AS A MEDIATOR THE EFFECT OF COMPENSATION ON EMPLOYEE PERFORMANCE - Mohyi, Achmad (Jurnal Ilmu Manajemen (JIMMU), 2022)
This study aims to analyze the effect of compensation on performance mediated by job satisfaction for Grab Bike drivers in Malang City, with a research sample of 96 respondents. The sampling technique in this study used the accidental sampling method, the data collection used the questionnaire method. While the data analysis method used is the path analysis method (path analysis).Â The results showed that there was a significant effect of compensation on performance. There is a significant effect of compensation on job satisfaction. There is a significant effect between job satisfaction on performance and it is proven that job satisfaction mediates the effect of compensation on performance.Â The researcher's suggestion from the results of this study is that it is expected that the management will make policies to increase incentives to increase job satisfaction and performance.Keyword: Job satisfaction, compensation, performance, Grab bike